Pemberdayaan Manajemen Kelompok Usaha Pengolah Abon Ikan Tuna Desa Gajaherjo, Kabupaten Malang - Tariaranie Wiraguna, Rayie; Buyung Adi D; Andi Basuki (Jurnal Pengabdian UntukMu NegeRI, 2021)
Gajahrejo Village is one of the partner villages located on the southern coast of Malang Regency. The business of processing fish into shredded fish in Gajahrejo village was initiated in early 2017, and until now, it is still a home industry managed by PKK women in Gajahrejo Village by forming a Joint Business Group (KUB). Each group consists of 3-5 people who work together in the production and packaging processes. So far, shredded products are only produced if there is an order. This is due to the lack of information related to good business management, the lack of human resources who have the skills to make shredded with a distinctive taste, packaging techniques that are still conventional, management systems that are still very simple, and also the absence of a promotion and marketing system-selling the right product. With these various problems, the solutions that were carried out were counseling related to correct fish processing, conducting training and mentoring on a good and correct business management system at KUB Gajahrejo village, and making a simple patent for the recipe for shredded fish that had been made. The resulting products have been marketed around the coastal tourist sites of South Malang.